Anti Cathepsin Antibody In Systemic Lupus Erythematosus - Nahla ghanim Abdul-majeed; Leen K. Mustafa Kamil; Mahmood Raheem Al-Rubaye (College of Pharmacy / Mustansiriyah University, 2013)
Antineutrophil cytoplasmic autoantibodies (ANCA) were found in patients with systemic lupus erythematosus (SLE). Cathepsin G was the major target antigen. However, some ANCA-positive sera did not recognize either of them.The present study was to investigate the unknown target antigens of ANCA (Cathepsin G) in patients with SLE and its relation to the activity of the disease (ds DNA ),C1q ,C3and C4. Seventy four SLE patients referred to immunological department in teaching laboratory\ medical city during period of (1st of march-31st of May) 2011 and 30 apparently healthy individual as a control group were subjected to Antinuclear antibody (ANA), Cathepsin G and C1q were detected by enzyme-linked immunosorbent assay (ELISA) technique.While dsDNA was detected by indirect immunofluorescent (IIF) technique and C3, C4 by single radial immunodiffusion (SRID). The age of SLE patients ranged between (4-71) years with mean age of 32.4. The mean C1q and Cathepsin G levels were 30.14 and 9.7 respectively with significant difference if compare it with the healthy control group. A significant result found between mean age of SLE patients and Cathepsin Ab of a P value 0.007. The Cathepsin G antibody was found in 26 (35%) of SLE patients with a significant P value (0.0001). The Cathepsin Ab were detected in 18 (43.9%) of a patients with positive ds DNA with no significant P value 0.078. while C1q Ab were detected in 38 (51.4%) of SLE patients and only 18 (47.4%) from them with Cathepsin Ab with statistically significant P value 0.024. Cathepsin Ab found in 19 (42.2%) of SLE patients with low level of C3 and only 6 (21.4%) of normal level of C3 with no significant P value0.076. This study showed 54(73.0%) of SLE patients had low level of C4 with no significant P value (0.15) and the Cathepsin Ab detected in 22 (40.7%) of them with no statistically significant P value 0.097. A statistically significant result were found for ANA, C1q,C3,C4 and Cathepsin Ab if we compare the result of SLE patients with control group, while The Cathepsin G antibody was found statistically significant in SLE patients ,with significant relation to C1q,on other hand no relation found with the activity of the disease (ds DNA ),C3 and C4 levels.